Crosstalk between epithelial sodium channels (ENaC) and basolateral potassium channels (Kir4.1/Kir5.1) in the cortical collecting duct. (7th February 2022) - Isaeva, Elena; Bohovyk, Ruslan; Fedoriuk, Mykhailo; Shalygin, Alexey; Klemens, Christine A.; Zietara, Adrian; Levchenko, Vladislav; Denton, Jerod S.; Staruschenko, Alexander; Palygin, Oleg
Abstract : Background and Purpose: Inwardly rectifying K + (Kir ) channels located on the basolateral membrane of epithelial cells of the distal nephron play a crucial role in K + handling and BP control, making these channels an attractive target for the treatment of hypertension. The purpose of the present study was to determine how the inhibition of basolateral Kir 4.1/Kir 5.1 heteromeric K + channel affects epithelial sodium channel (ENaC)‐mediated Na + transport in the principal cells of cortical collecting duct (CCD). Experimental Approach: The effect of fluoxetine, amitriptyline and recently developed Kir inhibitor, VU0134992, on the activity of Kir 4.1, Kir 4.1/Kir 5.1 and ENaC were tested using electrophysiological approaches in CHO cells transfected with respective channel subunits, cultured polarized epithelial mCCDcl1 cells and freshly isolated rat and human CCD tubules. To test the effect of pharmacological Kir 4.1/Kir 5.1 inhibition on electrolyte homeostasis in vivo and corresponding changes in distal tubule transport, Dahl salt‐sensitive rats were injected with amitriptyline (15 mg·kg −1 ·day −1 ) for 3 days. Key Results: We found that inhibition of Kir 4.1/Kir 5.1, but not the Kir 4.1 channel, depolarizes the cell membrane, induces the elevation of intracellular Ca 2+ concentration and suppresses ENaC activity. Furthermore, we demonstrate that amitriptyline administration leads to a significant drop in plasma K + level, triggering sodium excretion and diuresis. Conclusion and Implications: The present data uncover a specific role of the Kir 4.1/Kir 5.1 channel in the modulation of ENaC activity and emphasize the potential for using Kir 4.1/Kir 5.1 inhibitors to regulate electrolyte homeostasis and BP.